2020
DOI: 10.1186/s12890-020-1145-7
|View full text |Cite
|
Sign up to set email alerts
|

A case report of fungal infection associated acute fibrinous and organizing pneumonitis

Abstract: Background: Acute fibrinous and organizing pneumonitis (AFOP) is an uncommon variant of acute lung injury, characterized by intra-alveolar fibrin and organizing pneumonia. Proposed etiologies include connective tissue diseases, infections, occupational exposure, drug reactions, and autoimmune disease. Here we present a rare case of fungal infection associated AFOP in patient with diabetes mellitus (DM) and review the relevant literature. Case presentation: A 67-year-old man complained of cough, fever, dyspnea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The clinical manifestations of AFOP lack specificity and primarily manifest as shortness of breath, cough, and fever. AFOP may be related to numerous clinical conditions, such as infections, autoimmune diseases, adverse drug reactions, and environmental exposures (Table 2 ) [ 1 , 3 9 , 11 13 ]. There are no significant differences in the clinical and lung imaging manifestations of AFOP according to the cause.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical manifestations of AFOP lack specificity and primarily manifest as shortness of breath, cough, and fever. AFOP may be related to numerous clinical conditions, such as infections, autoimmune diseases, adverse drug reactions, and environmental exposures (Table 2 ) [ 1 , 3 9 , 11 13 ]. There are no significant differences in the clinical and lung imaging manifestations of AFOP according to the cause.…”
Section: Discussionmentioning
confidence: 99%
“…AFOP may improve following antibiotic treatment [ 14 ], suggesting that infection may trigger the onset of AFOP. Previous reports have shown that a variety of infections may be associated with AFOP, including bacterial infections ( Haemophilus influenzae , Acinetobacter baumannii ), viral infections (respiratory syncytial virus, influenza virus A/H1N1, human immunodeficiency virus), and fungal infections ( Pneumocystis jirovecii , Penicillium citrinum ) [ 1 , 5 9 ]. In the reported case, Legionella pneumonia was diagnosed based on a history of contact with soil before the onset; symptoms of fever, expectoration and shortness of breath; extrapulmonary manifestations (gastrointestinal symptom, liver function injury and hyponatremia), and the positive Legionella urine antigen test result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation